Both chemical and crystalline phase configuration influence the molecular features of humic acids in humic–calcium–phosphates fertilizers. Issue 44 (16th August 2019) - Baigorri, Roberto; Erro, Javier; Urrutia, Óscar; Martinez, José Manuel; Mandado, Marcos; Martín-Pastor, Manuel; García-Mina, José M.
Abstract : Phosphate–metal–humic complexes are very relevant in nature due to their crucial role in phosphate availability for plants and microorganisms. Abstract : Phosphate–metal–humic complexes are very relevant in nature due to their crucial role in phosphate availability for plants and microorganisms. Synthetic phosphate–calcium–humic acid (HA) complexes have proven to be efficient sources of available phosphorus for crops. However, the current knowledge about their structure and molecular features is very poor. The structural implications of phosphate interaction with humic binding sites through calcium bridges, in both monocalcium phosphate and dicalcium phosphate is investigated by using molecular modeling, 31 P-NMR, 1 H-NMR and X-ray diffractometry. The conformational changes in the molecular configuration of the humic acid involved in the interaction resulting from the synthetic process is also studied by using HPSEC and synchronous fluorescence. The results obtained allow us to identify the phosphate type in the crystalline phase that is involved in the interaction of humic acid binding sites and the different forms of calcium phosphate. Synchronous fluorescence also shows that whereas the conformational configuration of the HA binding site is only partially affected in the monocalcium phosphate interaction, it changes in the case of dicalcium phosphate showing simpler molecular arrangements. These changes in the molecular conformation of the binding site in HA in solution may influence the biological activity of the humic acid. On the other hand, HPSEC studies show that the humic–calcium–phosphate interaction is accompanied by increases in the humic acid apparent size distribution. This effect is more intense in the case of monocalcium phosphate system probably due the influence of pH.